2009
DOI: 10.1161/circresaha.108.185405
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Is Required for Endothelial Differentiation of Embryonic Stem Cells and Vascularization via Pathways Involving Both Wnt/β-Catenin and Protein Kinase Cα

Abstract: Abstract-In this study, we examined the signaling pathways activated by Wnt5a in endothelial differentiation of embryonic stem (ES) cells and the function of Wnt5a during vascular development. We first found that Wnt5a Ϫ/Ϫ mouse embryonic stem (mES) cells exhibited a defect in endothelial differentiation, which was rescued by addition of Wnt5a, suggesting that Wnt5a is required for endothelial differentiation of ES cells. Involvement of both ␤-catenin and protein kinase (PK)C␣ pathways in endothelial different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 45 publications
5
52
0
Order By: Relevance
“…Previous studies have shown that WNT signaling pathway played an important role in controlling morphogenesis in cardiac (4) and vascular (5) tissue development. WNT5a is a key signaling molecule that mediates endothelial cell proliferation and differentiation (5,29), while WNT11 plays an important role for cardiac development (4,30). Our results directly support the notion that the differential expression of these molecules within the EBs, potentially from nonmesoderm tissues, directly contributes to the differentiation of mesoderm precursors to either cardiac or endothelial pathways.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have shown that WNT signaling pathway played an important role in controlling morphogenesis in cardiac (4) and vascular (5) tissue development. WNT5a is a key signaling molecule that mediates endothelial cell proliferation and differentiation (5,29), while WNT11 plays an important role for cardiac development (4,30). Our results directly support the notion that the differential expression of these molecules within the EBs, potentially from nonmesoderm tissues, directly contributes to the differentiation of mesoderm precursors to either cardiac or endothelial pathways.…”
Section: Discussionsupporting
confidence: 79%
“…Those lineages arise from distinct mesoderm subpopulations that develop sequentially from premesoderm cells (3). Such lineage specification is highly coordinated with differential changes in gene expression (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Yang et al reported that Wnt5a is involved in the endothelial differentiation of ESCs via both Wnt/β-catenin and PKC signaling pathways and regulates embryonic vascular development. 93 Rho GTPases are involved in the self-renewal, multipotential differentiation ability, migration, and adhesion of stem cells. 94 In this study, F9 cells treated with RA or AgNPs showed upregulation of Rho expression, whereas the cells treated with RA or AgNPs plus cisplatin exhibited reduced expression of Rho, which confirms that cisplatin inhibits the AgNPs-induced Rho activation of differentiation in F9 cells.…”
mentioning
confidence: 99%
“…Endothelial cells are active participants and regulators of inflammatory processes (15). Wnt5a has been implicated in endothelial proliferation and migration (16)(17)(18), as well as endothelial differentiation of embryonic stem cells (19).…”
mentioning
confidence: 99%